The Effectivity of TPS Type Cooperative Learning Model Based on Interpersonal Intelligence Toward Mathematical Knowledge Competencies - Agustika, G.N. Sastra; Aryati, Ni Md. Ayu; Wiarta, I Wyn. (Journal of Education Reseach and Evaluation, 2019)
This study aimed to find out the effectiveness of cooperative learning model of the Think Pair Share type observed from interpersonal intelligence toward Mathematical competency on the fourth grade at SDN Moh. Hatta in academic year of 2018/2019. This study was a quasi-experimental design with 2 x 2 factorial design. The population of this study were 244 students on the fourth grade of SDN Moh. Hatta in academic year of 2018/2019. The sample technique used in this study was purposive sample.The data were collected using test and non-test methods. The data were analysed using 2-lane variance analysis. Based on the results of the analysis, it is obtained that (1) FA hitung = 7,002 > F tabel (α = 0,05; 1;76))= 3,967. Therefore, the null hypothesis (H0) is rejected. It signifies that “there is a significant difference in Mathematical competency between group of students who are taught through cooperative learning model of Think Pair Share type and group of students who are taught using conventional learning”, (2) FB hitung = 0,041 <  F tabel (α = 0,05; 1;76)) = 3,967. Therefore, the null hypothesis (H0) is accepted. It means that “there is no significant difference in Mathematical competency between students who have high interpersonal intelligence and students who have low interpersonal intelligence”, (3) FAB hitung = 0,902  < F tabel (α = 0,05; 1;76))= 3,967. From the last results, the null hypothesis (H0) is accepted. It means that “there is no significant interaction between cooperative learning model of Think Pair Share type and interpersonal intelligence on Mathematical competency. The results of the treatment effectiveness calculation obtained the score of 14Î·2=0.083"> . Overall, it can be concluded that the application of the learning model has an influence on the Mathematical competency by 8,3%